Analisis Kesalahan Bidang Sintaksis pada Buku Teks Pelajaran Bahasa dan Sastra Indonesia Untuk SMA dan MA Kelas X - Puspitasari, Dias Febriana, Prof. Dr. Markhamah, M.Hum (2016)
Textbooks have an important role in the learning process, because the textbook is able to provide information and useful knowledge for learners to supplement science, and for life in the future. The purpose of this study is to identify and explain the analysis form fields found in textbooks Indonesian language and literature for high school and MA class X. This type of research used in this research is qualitative research. The data in this study is the word, the phrase contained in the textbooks subjects Indonesian language and literature who have keslahan particularly in the field of syntax. Data collection techniques in this study using the techniques of documentation and refer to the note. Based on the data that has been analyzed, it was found nine field errors of syntax that includes, diction is not right in forming sentences 22%, logic sentence 2%, sentence structure are not standard 10%, the sentence is not clear 26%, the sentence ambiguous 8%, contamination sentence 2%, 24% use of redundant words, a loan word used in a sentence that is not exactly 2%, 8% coherence. Analysis of field syntax errors in textbooks to help facilitate teachers and students to understand the text reading, manual work on the problems, multiple choice questions and essays,elements, absorption off reign words wrong.